Evaluation of Dental Anxiety in Patients Undergoing Dentoalveolar Surgery with Laser Treatment - UĞURLU, FAYSAL (MARY ANN LIEBERT, INC, 2013)
Objective: The purpose of this study was to evaluate dental anxiety in patients undergoing apicectomy procedures performed with conventional instruments or an erbium-doped yttrium aluminum garnet (Er:YAG) laser. Methods: Twenty-eight patients undergoing apicectomy were divided into two groups; roots were removed with an Er: YAG laser in group A (n = 14) and with conventional instruments in group B (n = 14). All patients completed preoperative State-Trait Anxiety Inventories (STAI) and postoperative questionnaires. Results: Although state anxiety, trait anxiety, and postoperative questionnaire scores were lower in patients undergoing Er: YAG laser treatment than in those treated with conventional instruments, the differences were not statistically significant. Conclusions: Surgical instruments affect the anxiety levels of dental patients. Even with the STAI scores being lower for patients treated with Er: YAG, use of the Er: YAG laser alone cannot contribute to the resolution of dental anxiety. A patient's individual condition is the major factor influencing that patient's anxiety level.
Keywords: ER-YAG LASER; HARD SUBSTANCES; CHILDREN